2022
DOI: 10.1049/nbt2.12097
|View full text |Cite
|
Sign up to set email alerts
|

Lipid‐coated bismuth nanoflower as the thermos‐radio sensiti for therapy of lung metastatic breast cancer: Preparation, optimisation, and characterisation

Abstract: Lung metastatic breast cancer (LMBC) leads to a large number of deaths in women with breast cancer, and radiotherapy has been considered the common assay for tumour therapy except for surgery. However, radiotherapy still faces problems of low efficiency due to resistance and easily induced side effects. Here, the authors designed lipid‐decorated bismuth‐based nanoflowers (DP‐BNFs) as both a radiosensitiser and a photothermal therapy agent for LMBC treatment. The BNFs were prepared by oxidation of bismuth nitra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…These nanoflowers enhanced the therapeutic efficiency of both radiotherapy and photothermal therapy, indicating their potential as a multifunctional tool in the treatment of metastatic cancers. The lipid coating contributes to the biocompatibility and effective delivery of the nanoflowers, optimizing their interaction with cancer cells [7].…”
Section: Photosensitizers For Photodynamic Therapy (Pdt) and Radiothe...mentioning
confidence: 99%
See 2 more Smart Citations
“…These nanoflowers enhanced the therapeutic efficiency of both radiotherapy and photothermal therapy, indicating their potential as a multifunctional tool in the treatment of metastatic cancers. The lipid coating contributes to the biocompatibility and effective delivery of the nanoflowers, optimizing their interaction with cancer cells [7].…”
Section: Photosensitizers For Photodynamic Therapy (Pdt) and Radiothe...mentioning
confidence: 99%
“…Thermo-radiotherapy for lung metastatic breast cancer [7] Chlorin-lipid nanovesicle, 131I-labeled bovine serum albumin Chlorin e6 (Ce6), 131I Synergistic radiotherapy and Cerenkov radiation-induced photodynamic therapy [8] Lipid nanoparticles coated with TRAIL Apo2-Ligand/TRAIL (tumor necrosis factor-related apoptosis-inducing ligand) Induces apoptosis in tumor cells, overcomes resistance to soluble recombinant TRAIL [84] Solid lipid nanoparticles B13 (D-NMAPPD, a ceramidase inhibitor)…”
Section: Stimulator Of Interferon Genes Agonistmentioning
confidence: 99%
See 1 more Smart Citation
“…When exposed to light of specific wavelengths, the photothermal agents are activated to induce tumor cell destruction ( 88 ). Xue et al ( 89 ) devised a lipid-modified bismuth-based nanoflower, which was subsequently transformed into a dry powder inhaler, DP-BNF@Lat-MPs, using lactose spray-drying method after optimizing the preparation parameters. After assessing the expression levels of cleaved caspase-3, HSP70 and p-p65 within the respective cell groups, it was demonstrated that under the coexistence of near-infrared light (NIR) and infrared light (IR), the nanoparticles effectively facilitated the activation of the NF-κB pathway in tumor cells and induced cellular apoptosis ( 89 ).…”
Section: Preclinical Application Of Micron/nddsmentioning
confidence: 99%
“…Xue et al ( 89 ) devised a lipid-modified bismuth-based nanoflower, which was subsequently transformed into a dry powder inhaler, DP-BNF@Lat-MPs, using lactose spray-drying method after optimizing the preparation parameters. After assessing the expression levels of cleaved caspase-3, HSP70 and p-p65 within the respective cell groups, it was demonstrated that under the coexistence of near-infrared light (NIR) and infrared light (IR), the nanoparticles effectively facilitated the activation of the NF-κB pathway in tumor cells and induced cellular apoptosis ( 89 ). Another study investigated the therapeutic efficacy on lung metastasis breast cancer mice using similar material compositions under NIR/IR irradiation.…”
Section: Preclinical Application Of Micron/nddsmentioning
confidence: 99%